Young and Middle-Aged Schoolteachers Differ in the Neural Correlates of Memory Encoding and Cognitive Fatigue: A Functional MRI Study - Klaassen, Elissa B.; Plukaard, Sarah; Evers, Elisabeth A. T.; de Groot, Renate H. M.; Backes, Walter H.; Veltman, Dick J.; Jolles, Jelle (Frontiers in Human Neuroscience, 2016)
This investigation was inspired by growing evidence that middle-aged persons in a cognitively demanding profession might be characterized by subtle cognitive fatigue. We studied young and middle-aged male schoolteachers. They were compared in a study with functional magnetic resonance imaging to evaluate differences during successful memory encoding. The schoolteachers were additionally subjected to an induced fatigue condition involving the sustained performance of cognitively demanding tasks and to a control condition. Results showed age-related brain activation differences underlying behavioural performance including: 1) greater activation in middle-aged versus young teachers in bilateral prefrontal cortex (PFC) areas; and 2) differential fatigue effects in the left anterior cingulate cortex (ACC) depending on age group. Middle-aged schoolteachers showed decreased ACC activation in the fatigue compared to the control condition, whereas no change in activation was found in young teachers. Findings demonstrate age effects in these middle-aged subjects that are typically found in older adults, specifically in PFC over-activation. Findings also indicate that already in middle age cognitive aging may be associated with greater resource depletion following sustained task performance. The findings underscore the notion that persons in a cognitively demanding profession can experience subtle age effects, which are evident on fMRI and which impact daily functioning. Possible practical implications for middle-aged schoolteachers are discussed.